Inventory of Fish Types in Lubuk Larangan Area Batang Bungo River, Jambi Province - Rini Hertati; Mohd. Yusuf Amrullah; Sri Maryeni (Faculty of Fisheries and Marine, Universitas Riau, 2024)
The decreasing number of fish species caught by fishermen in the Batang Bungo River from year to year means that this study aims to inventory the types of fish caught in the Batang Bungo River. Hopefully, this inventory data can create a wealth of fishery resources in Indonesia. The research method uses the Purposive Sampling method. Data collection uses descriptive data. The research location is station I in the Lubuk larangan area people old Hamlet, Laman Panjang Hamlet, Station II in the Lubuk larangan area of ​​Tepian Lamo Hamlet, Rantau Pandan Hamlet and Station III in the Lubuk larangan area of ​​Belimbing, Tebat Hamlet, Batang Bungo River. The results of the research at Station I, the types of fish found were 2 Orders, two families, eight genera, and eight species; Station II fish caught 4 Orders, four families, ten genera, and ten species; and Station III types of fish caught as many as 4 Orders, four families, seven genera and seven species. The types of fish caught in the Batang Bungo River are five orders, five families, 15 genera, and 15 species